Studying CNS effects of Traditional Chinese Medicine using zebrafish models. (1st March 2021) - Wang, Dongmei; Hu, Guojun; Wang, Jingtao; Yan, Dongni; Wang, Mengyao; Yang, LongEn; Serikuly, Nazar; Alpyshov, Erik; Demin, Konstantin A.; Galstyan, David S.; Amstislavskaya, Tamara G.; de Abreu, Murilo S.; et al.
Abstract: Ethnopharmacological relevance: Although Traditional Chinese Medicine (TCM) has a millennia-long history of treating human brain disorders, its complex multi-target mechanisms of action remain poorly understood. Animal models are currently widely used to probe the effects of various TCMs on brain and behavior. The zebrafish ( Danio rerio ) has recently emerged as a novel vertebrate model organism for neuroscience research, and is increasingly applied for CNS drug screening and development. Aim of the study: As zebrafish models are only beginning to be applied to studying TCM, we aim to provide a comprehensive review of the TCM effects on brain and behavior in this fish model species. Materials and methods: A comprehensive search of published literature was conducted using biomedical databases (Web of Science, Pubmed, Sciencedirect, Google Scholar and China National Knowledge Internet, CNKI), with key search words zebrafish, brain, Traditional Chinese Medicine, herbs, CNS, behavior. Results: We recognize the developing utility of zebrafish for studying TCM, as well as outline the existing model limitations, problems and challenges, as well as future directions of research in this field. Conclusions: We demonstrate the growing value of zebrafish models for studying TCM, aiming to improve our understanding of TCM' therapeutic mechanisms and potential in treating brain disorders. Graphical abstract: Image 1